Flood Risk and Economic Loss Assessment in the Lower Citarum Basin Using InaSAFE - Rahmah Dara Lufira; Suwanto Marsudi; Ussy Andawayanti; Ery Suhartanto; M. Amar Sajali; Rizki Ramadhani Pratama (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
The hydrometeorological hazard of flooding in the Lower Citarum River Basin constantly affects agricultural sustainability, infrastructure, settlements, and regional economic activities. This study used InaSAFE to model human exposure and economic losses due to flooding under a 50-year return-period scenario. Flood depths were classified as >1.5 m (high), 0.76–1.5 m (medium), and ≤0.76 m (low) and then overlaid with spatial layers of population, land cover, roads, and buildings. The results revealed 1,739,195 exposed individuals, with 1,067,442 requiring evacuation support from medium-to high-depth classes. The different types of land cover exposed to floods cover 126,413 ha, mainly agricultural areas. The minimum humanitarian relief needs are US$ 88.00 million. The losses from buildings and public facilities totaled USD 616.51 million, and for road infrastructure, they amounted to USD 1.23 million, providing a subtotal of primary direct losses of USD 894.67 million. Additional proxy-based elements raised the stretched notional economic-loss estimate to USD 2.64 billion. These results offer a baseline for additional studies on flood-risk reduction and future scenario-based analyses of possible mitigation alternatives; they are not an explicit evaluation of the hydraulic or economic effectiveness of the Cijurey Dam.